Breeding of high biomass and lipid producing Desmodesmus sp. by Ethylmethane sulfonate-induced mutation. (May 2016) - Zhang, Yi; He, Meilin; Zou, Shanmei; Fei, Cong; Yan, Yongquan; Zheng, Shiyan; Rajper, Aftab Ahmed; Wang, Changhai
Highlights: EMS mutation could be used for breeding of Desmodesmus sp. successfully. High biomass and lipid production mutants S5 and G3 were obtained. The cells of mutant strains had higher contents of MUFAs and neutral lipids. The mutant strains had higher stability for producing biomass and lipid. Abstract: To improve the biomass yield and lipid productivity, two desert microalgae, Desmodesmus sp. S81 and G41 were induced mutagenesis by Ethylmethane sulfonate (EMS), and obtained two potential mutants, Desmodesmus sp. S5 and G3 from the mutagenic clones for their greatly promoted biomass and lipid production. The results showed that the biomass yield, lipid content and lipid productivity of the mutant strains S5 and G3 were 778.10 mg·L −1, 48.41% and 19.83 mg·L −1 ·d −1, 739.52 mg·L −1, 46.01%, and 17.92 mg·L −1 ·d −1, respectively, which presented the increment of 45.50%, 8.00% and 74.24%, 20.67%, 10.35% and 55.77% than those of S81 and G41. Comparing with the wild strains, the mutants showed reduced PUFAs and glycol lipids, elevated MUFAs and neutral lipids contents, which were appropriate for biodiesel production.